Показники працездатності конхоїдальних циліндричних прямозубих передач з підвищеною вантажопідйомністю. Теорія - Ткач, Павло Миколайович; Носко, Павло Леонідович; Башта, Олександр Васильович; Бойко, Григорій Олексійович; Герасимова, Ольга Вячеславівна (Національний технічний університет "Харківський політехнічний інститут", 2021)
Стаття присвячена актуальному завданню підвищення показників працездатності зубчастих приводів машин. Для вирішення зазначеного завдання у статті запропоновано застосувати конхоїдальне зачеплення, виготовлене зі зміщенням вихідного контуру та особливими умовами контакту. Особливістю запропонованого зачеплення є менша у порівнянні зі звичайним конхоїдальним зачепленням чутливість до похибок виготовлення та монтажу. У результаті теоретичних досліджень були визначені показники працездатності такого зачеплення. Областю застосування нового зачеплення є приводи машин для передачі великих потужностей.

The article is devoted to the actual problem of increasing the performance indicators of machine gear drives. To solve this problem, in the article proposed to use a conchoidal engagement made with a shifting of the reference profile and special contact conditions. A feature of the proposed engagement is that it is less sensitive to manufacturing and assembly errors compared to conventional conchoidal engagement. As a result of theoretical studies, the performance indicators of such an engagement were determined. This made it possible to determine the level of load during further experimental tests of new gears. Contact strength and meshing losses were selected as performance indicators subject to further experimental verification. The ratios of these indicators, calculated for conchoidal spur gears with convex-convex contact, made with a shifting of the reference profile, with similar involute ones, are theoretically determined. Comparative analysis of performance indicators was carried out for gears of involute and conchoidal engagement with the same parameters and shifting of the reference profile. It was found that for experimental conchoidal drives with shifting, the maximum load is 1.2 times higher than that of a similar involute drive with shifting, and the loss in engagement is 21% less. A rational area of application of the new gearing is machine drives for high power transmissions.
Performance indicators of conchoidal straight spur gears with increased loading capacity. The theory
Keywords: циліндричні зубчасті колеса; конхоїдальне зачеплення; зсув профілю; опукло-опуклий контакт; характеристики зчеплення; міцність поверхні зубців; втрата потужності зачеплення; conchoidal gearing; profile shift; convex-convex contact; meshing characteristics; teeth surface strength; gearing power loss